KULIAH KERJA MAHASISWA SEBAGAI WUJUD PENGABDIAN KEPADA MASYARAKAT DAN IMPLEMENTASI TRI DHARMA PERGURUAN TINGGI - Fatari Fatari; Rani Sri Sumarsih; Diah Permata Sari; Agus Maulana Yusuf; Ermiana Setiawati; Fildzah Hidayati; Ahmad Tomy Baedawi (Indonesian Collaboration Journal of Community Services, 2022)
Based on Law Number 12 of 2012 concerning Community Service which means that community service is one of the activities of the academic community by utilizing science and technology to educate the nation's life and improve the welfare of the community. The Tri Dharma of Higher Education are the three main pillars that become one of the components in achieving the vision and mission of each university. The Tridharma of Higher Education consists of Education and Teaching, Research, and Community Service. Every lecturer in higher education is obliged to carry out the Tri Dharma of Higher Education. The implementation method of Community Service (PkM) activities currently focuses more on the implementation of the Work Program that has been systematically prepared. It is carried out by KKM Group 15 Students and Field Supervisors by going directly to the field to visit the community and the data sources needed for questioning through direct interviews both personally and organizationally or data sources obtained through the village office or sub-district office. The conclusion provides an understanding of health and a healthy lifestyle. provide a wider contribution to the community through mentoring MSMEs and the creative economy in terms of developing promotions and online marketing so that income. the creation of Information Technology which has created a village website in order to facilitate information for village officials as well as for the surrounding community